Stimulation of histamine release from human basophils by human platelet factor 4. - Brindley, L L (1983)
Human basophils were stimulated to release histamine noncytotoxically by purified human platelet factor 4 (PF4) and the synthetic substituent peptide PF4(59-70). Histamine release was augmented significantly by 10(-7) M PF4 and 10(-5) M PF4(59-70), increased in a concentration-dependent manner, and attained a maximum at 3 X 10(-5) M PF4 and 3 X 10(-4) M PF4(59-70) similar to that achieved by goat anti-human myeloma IgE. PF4 (1-60) failed to initiate the release of histamine, which confirmed that the critical determinant of activity is in the carboxy-terminal sequence. Histamine release from basophils by optimally effective concentrations of PF4 and PF4(59-70) reached a plateau by 1-3 min, as contrasted with 10 min or longer for anti-IgE. The elimination of calcium and magnesium from the buffer suppressed the release of histamine by anti-IgE by 79-83%, but had no effect on that elicited by PF4(59-70). The rate of uptake of [125I]PF4 by purified basophils was similar on a molar basis to the rate of release of histamine by the same concentrations of PF4. The noncytotoxic release of histamine from human basophils by PF4 thus is temporally and biochemically distinct from that mediated by IgE and may be similar to that evoked by other polycationic stimuli.